The Use of Aquatic Mammals for Bait in Global Fisheries - Mintzer, Vanessa J.; Diniz, Karen; Frazer, Thomas K. (Frontiers in Marine Science, 2018)
The use of aquatic mammals as bait to enhance the harvest of fisheries species has garnered little attention by the scientific and conservation communities, often receiving only brief mention in reports focused on the human consumption or bycatch of aquatic mammals. A number of studies, however, highlight the negative impact of this practice on affected mammal populations. A systematic review of relevant literature published since 1970 yields new insight into the scope of the issue. Findings indicate that the practice of using aquatic mammals for bait has been and continues to be geographically widespread, has affected at least 42 species, and often involves deliberate killing for the express purpose of securing bait. The nature of the fisheries involved is diverse, encompassing a wide range of target species and gear types; however, shark fisheries that employ longlines appear to be the most widely engaged in using aquatic mammals as bait. This practice appears to be most common in Latin America and Asia. It is evident, based on our review, that there is little information on the impact of the direct take on most targeted mammal populations, commonly small cetaceans, and increased monitoring efforts are needed in many locales. In most instances, the ecology and population dynamics of the targeted fishery species is poorly understood and in some cases the species is classified as threatened, suggesting a greater fishery sustainability issue that cannot be fully addressed with a substitute for the aquatic mammal bait. It is essential that natural resource managers implement mitigation approaches that consider the socio-economic, cultural, political, and ecological circumstances leading to the use of aquatic mammal bait in each fishery.